The Presidio and Militia on the Northern Frontier of New Spain: A Documentary History, Volume Two, Part Two The Central Corridor and the Texas Corridor, 1700-1765 - Hadley, Diana; Schuetz-Miller, Mardith K.; Naylor, Thomas H. (University of Arizona Press, 2021)
Joining an acclaimed multivolume work funded by the National Historical Publications and Records Commission is a new volume of The Presidio and Militia on the Northern Frontier of New Spain. As the work of the Documentary Relations of the Southwest project, under the general editorship of Charles W. Polzer, S.J., the volumes stand alone in their translation and publication of a wide variety of documents that describe the Spanish exploration and conquest of what is now the southwestern United States and northern Mexico. The presidial system of northern New Spain's Central and Texas Corridor was an evolving institution used for exploration, military presence and defense against foreign powers, local militia duty, mission support, personal service, and penal obligations. The new volume, which covers parts of what is now Texas, New Mexico, and Mexico, includes letters, diaries, judicial papers, military reports, and interrogations. Difficult for researchers to access and sometimes to decipher, the records are presented in Spanish and in English translation, annotated and introduced by the volume editors.